Plaque-like Myofibroblastic Tumor: 2 Cases of This Unusual Dermal Tumor Which Occurs in Infancy and Early Childhood. (September 2018) - Sekar, Thivya; Mushtaq, Jameel; AlBadry, Waleed; Soole, Frederick; Nagy, Anita; Powell, Barry; Chong, Heung
Plaque-like myofibroblastic tumor (PLMT) is a rare dermal spindle cell tumor which occurs in infancy or childhood within the first 4 years of life. The tumor is often pruritic and mostly presents on the lower back. We describe 2 cases with characteristic clinical and histological features of this entity, thus adding to the 10 cases which have so far been reported. Histologically, the lesion resembles a dermatofibroma. However, diffuse and uniform immunohistochemical staining with smooth muscle actin favors a myofibroblastic lineage. PLMT should be considered in the differential diagnosis of a dermal spindle cell tumor in the pediatric age-group.